In UPM- EANET Acid Deposition Project : Soil and Plant Responses to Simulated Acid Rain Treatments - Susilawati, Kasim; Mohamad Hilmi, Ibrahim; Osumanu Haruna, Ahmed; Nik Muhamad, Nik Majid (2011)
Acid rain is one of the environmental problems in some countries. There is dearth of information on the effect of acid rain on tropical forest soils and plants. Thus two studies were conducted to: (1) determine the effect of Simulated Acid Rain (SAR) on selected forest plants species, and (2) determine the effect of SAR on selected soil chemical properties. These studies were conducted in laboratory and glasshouse at Universiti Putra Malaysia Bintulu Sarawak Campus. Rainwater was captured and analyzed weekly for 6 months before it was used in this study. The rain water was mixed with a mixture of concentrated H2SO4 and HNO3 [3:2(v/v)] to produce different levels of SAR before they were applied to soils. Kelat (Syzygium campanulatum) and Andira (Andira surinamensis) were propagated for 5 months after which they were transplanted into pots. Plant growth was measured using standard methods. Plant and soil samples were collected every two weeks for two months. Secondly soil samples were treated with six concentrations of SAR [pH 3.5, 4.0, 4.5, 5.0, 5.5, and control (6.03)] at two different times (4 and 15) in the laboratory. They were left for 45 days. Soil samples were taken and analyzed using standard procedures. The heights of the plants decreased with increasing concentrations of SAR. The decreased of 36 and 29% for S. campanulatum and A. surinamensis, respectively were probably due to either foliar injury or Al toxicity or both. The chemical characteristics such as exchangeable Ca of the incubated soil were affected by SAR application. The 4 times frequency of SAR application gave more effect as compared to 15 times frequency. Carbon dioxide from microbial activity promotes carbonic acid production and this leads to soil pH reduction. S. campanulatum is more sensitive to acid rain however a field study should be carried out to validate the results of this experiment. SAR frequency and pH play an important role in altering soil chemical properties but a study needs to be conducted to verify these results.